The Role Of Online Motorcycle Tickets In Reducing The Unemployment Rate And Increasing Public Purchase Power In Makassar City - Idris, Muhammad; Winarti, Winarti (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This descriptive qualitative research examines the role of online motorcycle taxi (ojek online) work in reducing unemployment and increasing people’s purchasing power in Makassar City. The research method employed in-depth interviews with seven informants consisting of five online motorcycle taxi drivers and two supporting informants selected through purposive sampling. Data analysis used the Miles, Huberman, and Saldana model with stages of data reduction, data presentation, and conclusion drawing. The findings show that the gig economy through online motorcycle taxi work has successfully absorbed a diverse workforce, in which 40% of drivers come from unemployed groups, 35% are workers who shifted professions, and 25% take it as a side job. The main driving factors include economic needs, flexible working hours, easy access with simple requirements, and technological application support. Economically, drivers earn IDR 100,000–200,000 per day or IDR 2–5 million per month, which has proven sufficient to meet basic family needs with a surplus for savings and increased purchasing power. The overall socioeconomic impacts are positive, including increased accessibility to urban mobility, the development of MSMEs through GoFood services that increase turnover by 40–60%, as well as the expansion of drivers’ social networks. Although there are challenges such as income fluctuations depending on weather and economic conditions and conflicts with conventional transportation modes, digital transformation in transportation has proven effective in addressing employment issues in the digital economy era. This research contributes to understanding how innovations in urban mobility create a sustainable economic ecosystem with low barriers to entry, while also driving the micro economy and improving the welfare of Makassar City residents through comprehensive implementation of the gig economy.